Textural, Color, and Sensory Analysis of Cookies Prepared with Hemp Oil-Based Oleogels - Ana Leahu; Cristina Ghinea; Sorina Ropciuc; Cristina Damian (Gels)
The amount of saturated fat in cookies can be reduced by replacing margarine with oleogel, resulting in healthier products. In this study, the rheological and textural profile of cookies formulated with oleogel as the main margarine substitute was evaluated. Hemp seed vegetable oil was oleogelized with four types of waxes: beeswax (BW), carnauba wax (CW), candelilla wax (DW), rice bran wax (RW), and three oleogeling agents, sitosterol (S), pea protein (PP), and xanthan gum (XG), respectively. The textural and rheological properties of the oleogel dough samples were analyzed using the PertenTVT-6700 texturometer (Perten Instruments, Sweden) and the Haake rheometer. The results showed an increase in the hardness of cookie doughs with oleogels. The values of the elastic component (G′) and the viscous component (G″) increased, which means that the oleogels used affected the rheological behavior at 25 °C, causing an increase in the dough consistency. Sensory attributes, texture, and color parameters of cookies with oleogels were determined. The cookies’ hardness increased significantly from 4409.83 ± 0.13 g (control sample) to 7085.33 ± 0.15 g in the cookie sample prepared with hemp oil sitosterol oleogel, whereas the sample with candelilla wax had the lowest hardness value of 4048.09 ± 0.14 g. The color of the oleogel cookies was darker than that of the control cookies. The cookie sample with hemp oil and beeswax oleogel was the most appreciated by the evaluators among the oleogel cookie samples. The findings suggest that hemp seed oil oleogel is an effective fat substitute in cookies, promoting the application of this vegetable oil in food products.